Monte Carlo simulations for the space radiation superconducting shield project (SR2S). (February 2016) - Vuolo, M.; Giraudo, M.; Musenich, R.; Calvelli, V.; Ambroglini, F.; Burger, W.J.; Battiston, R.
Abstract: Astronauts on deep-space long-duration missions will be exposed for long time to galactic cosmic rays (GCR) and Solar Particle Events (SPE). The exposure to space radiation could lead to both acute and late effects in the crew members and well defined countermeasures do not exist nowadays. The simplest solution given by optimized passive shielding is not able to reduce the dose deposited by GCRs below the actual dose limits, therefore other solutions, such as active shielding employing superconducting magnetic fields, are under study. In the framework of the EU FP7 SR2S Project – Space Radiation Superconducting Shield – a toroidal magnetic system based on MgB2 superconductors has been analyzed through detailed Monte Carlo simulations using Geant4 interface GRAS. Spacecraft and magnets were modeled together with a simplified mechanical structure supporting the coils. Radiation transport through magnetic fields and materials was simulated for a deep-space mission scenario, considering for the first time the effect of secondary particles produced in the passage of space radiation through the active shielding and spacecraft structures. When modeling the structures supporting the active shielding systems and the habitat, the radiation protection efficiency of the magnetic field is severely decreasing compared to the one reported in previous studies, when only the magnetic field was modeled around the crew. This is due to the large production of secondary radiation taking place in the material surrounding the habitat.